Effects of grass competition on tree seedlings growth under different light and nutrient availability conditions in tropical dry forests in India. Issue 5 (18th May 2020) - Bhadouria, Rahul; Srivastava, Pratap; Singh, Rishikesh; Tripathi, Sachchidanand; Verma, Pramit; Raghubanshi, Akhilesh Singh
Abstract: The interactive effects of light, nutrient availability and grass competition on seedlings of four tropical dry forest tree species, namely, Indian jujube ( Ziziphus mauritiana ), arjun ( Terminalia arjuna ), gum arabic ( Acacia nilotica ) and catechu ( Acacia catechu ), were evaluated in an experimental study at Banaras Hindu University, Varanasi, India. Full‐ and reduced‐ (20% of the full) sunlight, no‐nutrient and nutrient supplementation, and presence of grass and no‐grass conditions were taken in a split‐plot design to observe the effects on the plant growth and leaf nutrient parameters. We observed a significant interaction between light and nutrient availability on total dry weight and relative growth rate for the tree seedlings of all the species. Seedling growth was lower in presence of grass under full sunlight condition with/without nutrient addition, and also under reduced sunlight condition with nutrient addition. However, leaf‐N and ‐P concentration showed slight increase following nutrient addition across the species and light conditions. All the species responded positively to nutrient addition irrespective of light and grass conditions. Our study further indicates that nutrient addition under reduced light condition in tropical dry forests may be a possible strategy to ameliorate the negative impact of grasses on tree seedling growth. Overall, a better understanding of tree seedling establishment in the presence of grasses is of utmost importance for the development of management plans that may improve the diversity of tree species in tropical dry forests. Abstract : This research article is based on the central idea of how different tree species (belonging to the different functional group) seedlings (growth attributes and leaf‐N and ‐P concentration) behave under nutrient addition in the variable influence of light and grass conditions in a dry tropical ecosystem. This study indicates that, under the global atmospheric N deposition scenario, greater increase in the soil nitrogen may provide a better edge to grasses over tree seedlings, which may have implications for community structure and vegetation dynamics in tropical dry forests.